Unilateral Balance, Muscular Strength, Foot Arch Status, and Physical Performance in Young Adults with and Without Low Back Pain - Mansour Abdullah Alshehri; Hammad Alhasan (Journal of Clinical Medicine, 2026)
Background/Objectives: Low back pain (LBP) is a major cause of disability worldwide. In Saudi Arabia, research has predominantly focused on its prevalence and associated risk factors, with comparatively limited evidence directly comparing balance, muscular strength, foot characteristics, and physical performance between young adults with and without LBP. This study therefore compared unilateral balance and handgrip strength between young adults with and without LBP, with foot arch status, walking performance, and lower limb functional capacity examined as secondary outcomes. Methods: This study employed a cross-sectional observational design and enrolled 55 young participants (25 with LBP and 30 healthy controls). The primary outcomes included unilateral balance, measured using the Single-Leg Stance Test (SLST) with eyes open and eyes closed, and handgrip strength. Secondary outcomes included foot arch status, assessed using the Sit-to-Stand Navicular Drop Test (SSNDT), walking performance using the 10-Metre Walk Test (10-MWT), and lower limb functional capacity using the 30-s Chair Stand Test (30s-CST). SLST duration was analysed using generalized estimating equations, whereas multivariable linear regression models were used for the remaining outcomes. All adjusted analyses accounted for age, body mass index, sex, smoking status, athletic status, and limb dominance where appropriate. Results: Participants with LBP demonstrated significantly poorer unilateral balance than healthy controls after adjustment, with significant main effects of group on both the right and left SLST. Significant group-by-visual condition interactions were observed for both limbs, indicating that between-group differences were greater under eyes-closed conditions. Handgrip strength was lower in participants with LBP in the unadjusted models; however, these between-group differences were no longer significant after adjustment. No significant adjusted between-group differences were observed for SSNDT scores, walking speed, or 30s-CST performance. Among the adjustment variables, male sex, right leg dominance, and athletic status were associated with better performance, whereas increasing age and smoking were associated with poorer performance. Conclusions: Young adults with LBP demonstrated poorer unilateral balance than healthy controls, with between-group differences being greater under eyes-closed conditions. In contrast, no significant adjusted between-group differences were observed for handgrip strength, foot arch status, walking performance, or lower limb functional capacity. These findings identify unilateral balance, particularly under reduced visual input, as a functional domain that differed between groups in this young adult sample.